Job Hunting & Get Hired - Wan Norfazilah, Wan Ismail; Shamsul, Zakaria (Penerbit UMP, 2021)
This book is an essential reading for anyone interested in catching and applying job hunting tips. Job hunters, especially university graduates, can learn many excellent ways to steer on the right route in chasing and finally anding their dream jobs from this book. The simple step-by-step descriptions and samples provided in this book cover drafting a resume, writing a thank you email after an interview, and preparing for interviews, to name just a few. The gamut of job-search basics makes this book an excellent guidance for fresh graduates to secure their first jobs at the right time. Read and find the voice and style you prefer to get through your job search.